2013
DOI: 10.4102/jsava.v84i1.535
|View full text |Cite
|
Sign up to set email alerts
|

Schmallenberg virus – Is it present in South Africa?

Abstract: In July 2006, a case of two out of three lambs born to one ewe in a flock of 45 had signs that, in retrospect, were possibly consistent with Schmallenberg virus infection. This occurred in the Onderstepoort area (Gauteng Province) but a definitive diagnosis was not made. Then, in May 2008, a farmer in the Delmas area (Mpumalanga Province) reported that deformed lambs had been born to several ewes in the flock. Six of the approximately 50 mated ewes gave birth to lambs showing varying degrees of arthrogryposis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…The overall seroprevalence was estimated to be 24.5% (Azkur et al, 2013). This observation and the results described in another report about congenital abnormalities in South African ruminants (Leask et al, 2013) raised questions on the origin and distribution of SBV and of closely related viruses of the Simbu serogroup, which so far comprises eight recognized species. As Culicoides spp.…”
Section: Introductionmentioning
confidence: 89%
“…The overall seroprevalence was estimated to be 24.5% (Azkur et al, 2013). This observation and the results described in another report about congenital abnormalities in South African ruminants (Leask et al, 2013) raised questions on the origin and distribution of SBV and of closely related viruses of the Simbu serogroup, which so far comprises eight recognized species. As Culicoides spp.…”
Section: Introductionmentioning
confidence: 89%
“…Moreover, the detection of seropositive animals among exotic and indigenous cattle located in different geographical regions of Nigeria suggests that the disease is not breed-restricted and that the virus is present over a large area of the country, being likely sustained by the activity of Culicoides vectors. Except for the report of suspected SBV infection in South Africa (Leask et al, 2013) and recent serologic evidence of the disease in Mozambique (Blomstrom et al, 2014), the infection has so far been reported only from Europe and Asia (Doceul et al, 2013;Azkur et al, 2013). Therefore, our detection of seropositive cattle in Nigeria indicates that SBV infection may actually be more widespread in distribution than previously believed.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from a retrospective report of suspected SBV infection of lambs in South Africa and the recent detection in Mozambique of SBV antibodies in ruminants (Leask et al, 2013;Blomstrom et al, 2014), there is limited information on the disease in Africa. In Nigeria, although there are no reports of SBV infection in ruminants hitherto, congenital malformations associated with SBV such as arthrogryposis, kyphosis, scoliosis and brachygnathia inferior have been reported among Nigerian ruminants (Ibrahim et al, 1987;Ate & Allam, 2002;Ibrahim et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…There is no historical evidence of the presence of SBV in Germany before 2011 (Gerhauser et al., ; see Data S1 and S2). The detection of SBV‐induced antibodies outside western Europe (Turkey, sera from 2006) (Azkur et al., ) and in Africa (South Africa, 2008; Mozambique, September 2013; Blomstrom et al., ; Leask, Botha, & Bath, ) might be seen as probable cross‐reactions with other orthobunyaviruses. The detection of stillbirths and congenital malformations was recorded rapidly after the first virus notification in northern Europe (the Netherlands [8 December 2011], Belgium [22 December 2011], France [25 January 2012]) (De Regge et al., ; Gache et al., ; Veldhuis et al., ; Zanella et al., ) and with a short delay in southern Europe (Italy [6 February 2012], Spain [March 2012]) (Balseiro, Royo, Gomez Antona, & Garcia Marin, ; Monaco et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…There is no historical evidence of the presence of SBV in Germany before 2011 (Gerhauser et al, 2014; see Data S1 and S2). The detection of SBV-induced antibodies outside western Europe (Turkey, sera from 2006) (Azkur et al, 2013) and in Africa (South Africa, 2008;Mozambique, September 2013;Blomstrom et al, 2014;Leask, Botha, & Bath, 2013) Gache et al, 2013;Veldhuis et al, 2013;Zanella et al, 2015) and with a short delay in southern Europe (Italy [6 February 2012], Spain [March 2012]) (Balseiro, Royo, Gomez Antona, & Garcia Marin, 2015; Monaco et al, 2013). Retrospective studies conducted in several European countries showed (i) the detection of SBV-specific antibodies in domestic and wild ruminants starting autumn 2011 in a large area covering Belgium, the Netherlands, France, Germany, southern Sweden, with a high level of seroprevalence observed in domestic ruminants (Chenais et al, 2015;Laloy et al, 2014;Linden et al, 2012;Meroc et al, 2013Meroc et al, , 2014Mouchantat et al, 2015;Rossi et al, 2015;Veldhuis et al, 2013;Wernike, Jost et al, 2014;Wernike, Silaghi et al, 2014;Zanella et al, 2015); (ii) the detection of SBV-specific antibodies in wildlife animals in December 2011 shortly after the first notified case and rapidly very far from the detection point: in the south-western part of France (Hautes-Pyr en ees department) from wildlife animal sera in December 2011 (Laloy et al, 2014;Rossi et al, 2015); (iii) the detection of virus circulation in Culicoides populations starting August 2011 in northern Europe with a probable date of virus introduction in Belgium estimated early to mid-July 2011 (De Regge et al, 2012, 2014) (see Data S1 and S2).…”
Section: Introductionmentioning
confidence: 99%